2004
DOI: 10.1007/s00170-003-1898-1
|View full text |Cite
|
Sign up to set email alerts
|

Tool wear monitoring in ramp cuts in end milling using the wavelet transform

Abstract: Tool wear identification and estimation present a fundamental problem in machining. With tool wear there is an increase in cutting forces, which leads to a deterioration in process stability, part accuracy and surface finish. In this paper, cutting force trends and tool wear effects in ramp cut machining are observed experimentally as machining progresses. In ramp cuts, the depth of cut is continuously changing. Cutting forces are compared with cutting forces obtained from a progressively worn tool as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Recent studies deliver quantifiable evidence that wear leads to an increase in energy consumption to perform the same task [28]. To monitor the process of wear, among other things technologies from aviation industries are applied [29].…”
Section: C) Wearmentioning
confidence: 99%
“…Recent studies deliver quantifiable evidence that wear leads to an increase in energy consumption to perform the same task [28]. To monitor the process of wear, among other things technologies from aviation industries are applied [29].…”
Section: C) Wearmentioning
confidence: 99%
“…There are studies that deliver quantifiable evidence that wear leads to an increase in energy consumption while producing similar parts [25]. Energy monitoring is applied in aerospace industries.…”
Section: Wearmentioning
confidence: 99%
“…Du [13] et al recognized the tool wear state through fuzzy decision trees, fuzzy linear function, fuzzy C-means algorithm and BP neural network, the identification rates of various methods showed that the fuzzy decision tree and fuzzy linear function were superiors. Choi [14] et al characterized the trend of cutting force using the approximate amount in the db5 wavelet analysis, and assessed tool wear state through the trend of cutting force. Kuljanic and Sortino [15] defined the normalized cutting force (NCF) indicator and the torque-force distance (TFD) indicator by cutting forces, and characterized the tool wear state through these two indicators.…”
Section: Introductionmentioning
confidence: 99%